THE VISUAL INVESTOR: HOW ARE NOVICE INVESTORS TRANSACTING SHARIA STOCK - Salman Nasution; Purnama Ramadani Silalahi; Muhammad Hafiz; Ismail Ghifari (Proceeding International Seminar of Islamic Studies, 2021)
The phenomenon of transacting sharia stock for novice investors is the spearhead of stock movements in Indonesia. Novi`ce investors should consider several important aspects in making transacting sharia stock. This study aims to determine how much influence the quality of accounting information, subjective norms, and perceived behavioral control of sharia stock investment decisions. This research uses a quantitative approach with multiple linear regression analysis. Data collection comes from distributing questionnaires to stock investors of members of the KSPMS Golden UIN North Sumatra through Google Form. The results of this analysis find the quality of accounting information (X1) and subjective norms (X2) have no significant effect partially on sharia stock investment decision making (Y). While the perceived behavioral control (X3) has a significant impact on (Y). The F Test results obtained that the F count F table is 16.531 2.81 with a significance value of 0.000 0.05, it can be concluded that X1, X2, and X3 have a significant simultaneous effect on Y. This research is quite important where novice investors can be the initial spearhead of smart investors, able to educate the public, and not be emotional.Keywords: Novice Investors, Transacting Sharia Stock